2012
DOI: 10.1093/brain/aws114
|View full text |Cite
|
Sign up to set email alerts
|

No inherent left and right side in human ‘mental number line’: evidence from right brain damage

Abstract: Spatial reasoning has a relevant role in mathematics and helps daily computational activities. It is widely assumed that in cultures with left-to-right reading, numbers are organized along the mental equivalent of a ruler, the mental number line, with small magnitudes located to the left of larger ones. Patients with right brain damage can disregard smaller numbers while mentally setting the midpoint of number intervals. This has been interpreted as a sign of spatial neglect for numbers on the left side of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 71 publications
(113 reference statements)
11
57
1
Order By: Relevance
“…Furthermore, our findings are in line with previous studies that illustrate dissociation between numerical and spatial mechanisms6, 7, 8, 9, 10 as no relationship was observed between numerical magnitude biases and any lateralized spatial attention bias. Thus, our findings support the generalized notion of hemispheric allocation of numerical magnitude 8, 10…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, our findings are in line with previous studies that illustrate dissociation between numerical and spatial mechanisms6, 7, 8, 9, 10 as no relationship was observed between numerical magnitude biases and any lateralized spatial attention bias. Thus, our findings support the generalized notion of hemispheric allocation of numerical magnitude 8, 10…”
Section: Discussionsupporting
confidence: 93%
“…Previous neuropsychological studies have demonstrated that right hemisphere fronto‐parietal lesions that invoke a rightward spatial attentional bias can induce an isomorphic pathological bias toward larger magnitudes 5. Critically, subsequent research has illustrated that such pathological biases in numerical magnitude allocation are dissociated from any spatial attention bias 6, 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By now several studies have reported that there is no correlation (e.g. Aiello et al, 2012;Ashkenazi & Henik, 2010). Of course null findings are hard to interpret.…”
Section: Bisection Bias In Neglect: a Role For Working Memorymentioning
confidence: 92%
“…However, evidence for this common processing is mixed. For example, supporting data come from the similarity of performance in number, time, or space processing (e.g., Brannon, Suanda, & Libertus, 2007;Zorzi, Priftis, & Umiltà, 2002), but the opposite possibility-that number, time, and space may each be fully independent-is supported by TMS and lesion studies showing dissociations among these dimensions (e.g., Aiello et al, 2012;Dormal, Seron, & Pesenti, 2006;Doricchi, Guariglia, Gasparini, & Tomaiuolo, 2005). A third, intermediate, possibility is that number, time, and space are only partly independent (e.g., Walsh, 2003).…”
Section: Introductionmentioning
confidence: 99%